4 Effect of Inclusion Rate of Silage With or Without the Presence of Alpha-Amylase on Feedlot Performance, Carcass Characteristics, and Efficiency Measures - Rusche, Warren C (J Anim Sci, 2020)
One hundred ninety-two Continental × British steers (initial BW 420 kg [SD 24.7]) were used in a randomized complete block design finishing study to evaluate the effects of feeding two types of silage germplasm at two inclusion rates. A 2 × 2 factorial arrangement of treatments was used with either a conventional (CON) or increased expression of alpha-amylase (Enogen, Syngenta Seeds, LLC, ENO) hybrid fed at either 12% (12SIL) or 24% (24SIL) of diet DM. Steers were blocked (n = 5) and assigned randomly within block to treatments, resulting in five pens and 48 steers per treatment. Steers were harvested after 126 (12SIL) or 140 (24SIL) days on feed. There were no silage source by inclusion rate interactions detected for live growth performance. Silage source did not affect live based average daily gain (ADG), gain to feed ratio (G:F), or final BW (FBW; P ≥ 0.35). Feeding 24% silage reduced ADG (P = 0.04) and G:F (P = 0.01) but increased FBW (P = 0.02) compared to 12SIL. A source by inclusion rate interaction was detected (P = 0.04) for calculated yield grade (YG) with steers fed 24% silage having increased YG within CON but not ENO. Hot carcass weight and ribfat were unaffected by silage source (P ≥ 0.81), but were increased by feeding 24% silage (P = 0.03 and P = 0.02, respectively). Feeding increased amounts of silage increased beef produced per hectare (P = 0.05). Conventional silage produced more beef per hectare (P < 0.01) due to differences in silage yield, but source of silage did not affect feedlot performance independent of silage yield. Feeding increased amounts of silage reduced DM efficiency on a live animal basis but increased beef produced per hectare which is of major value to cattle feeders who produce the majority of their own feedstuffs.